Sensitivity to CP discovery in the presence of Lorentz invariance-violating potential at T2HK/T2HKK - Supriya Pan; Kaustav Chakraborty; Srubabati Goswami (European Physical Journal C: Particles and Fields, 2024)
Abstract The investigation of conservation/violation of conjugation and parity (CP) symmetry in the leptonic sector is essential to understanding the evolution of the universe. Lorentz invariance and CPT are fundamental symmetries of nature. The violation of Lorentz invariance can also lead to CPT violations. The standard three-flavor neutrino oscillation framework presents a scenario for observing the signature of Lorentz invariance and CP violations. This work focuses on the effect of Lorentz invariance-violating parameters on the sensitivity to CP violation. We investigate the sensitivity in two proposed configurations of the upcoming T2HK experiment: (i) one detector each placed at 295 km and 1100 km, and (ii) two identical detectors at 295 km. This study probes the effect of CPT-violating parameters $$a_{eμ },a_{eτ },a_{μ τ }$$ a e μ , a e τ , a μ τ .